Analisis Realitas Pendidikan Dasar dalam Keterbatasan: Studi Kasus Sekolah Jarak Jauh SDN 1 Windubite, Kecamatan Poli- Polia, Kabupaten Kolaka Timur - Eva Safitri Maladeni (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Using SDN 1 Windubite as a case study, this research investigates how primary education is implemented in remote-distance schools located in rural areas. The study focuses on the conditions of the learning process, the inhibiting and supporting components, and the adaptive strategies employed by teachers and students. A qualitative case study approach was used, with data collected through documentation, interviews, and field observations. The data were analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The findings reveal that the main challenges faced by students include limited infrastructure—such as transportation access, school facilities, electricity, and internet connectivity—shortages of teaching staff, and students’ socio-economic conditions. However, collaboration with the local community, the use of alternative learning media, and contextual learning based on local values serve as adaptive strategies. This study concludes that strengthening educational equity policies, empowering teachers, and engaging community participation are strategic solutions to reduce educational disparities in remote areas.